2011
DOI: 10.1152/jn.00163.2011
|View full text |Cite
|
Sign up to set email alerts
|

Unpredictable elbow joint perturbation during reaching results in multijoint motor equivalence

Abstract: Motor equivalence expresses the idea that movement components reorganize in the face of perturbations to preserve the value of important performance variables, such as the hand's position in reaching. A formal method is introduced to evaluate this concept quantitatively: changes in joint configuration due to unpredictable elbow perturbation lead to a smaller change in performance variables than expected given the magnitude of joint configuration change. This study investigated whether motor equivalence was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
152
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(165 citation statements)
references
References 51 publications
11
152
2
Order By: Relevance
“…Although there were clear descriptive frequency differences in bat-ball contacts between participants, which is consistent with previous literature (Dicks et al, 2010), these descriptive differences were not statistically significant (our analysis for bat-ball contacts did not include speed as a covariate which may influence this finding). This finding implies that motor equivalence may be an underlying mechanism of visual control of action in expert striking skills, which has been reported for other motor skill tasks, such as reaching towards a target (Mattos et al, 2011). Anecdotally, it is apparent from observing different sport performers that their exists multiple movement patterns to achieve the relevant motor skill goal, but again, further investigation is required possibly using the methodology in this study to determine if motor equivalence is a consistent underlying mechanism of expertise in striking sports.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although there were clear descriptive frequency differences in bat-ball contacts between participants, which is consistent with previous literature (Dicks et al, 2010), these descriptive differences were not statistically significant (our analysis for bat-ball contacts did not include speed as a covariate which may influence this finding). This finding implies that motor equivalence may be an underlying mechanism of visual control of action in expert striking skills, which has been reported for other motor skill tasks, such as reaching towards a target (Mattos et al, 2011). Anecdotally, it is apparent from observing different sport performers that their exists multiple movement patterns to achieve the relevant motor skill goal, but again, further investigation is required possibly using the methodology in this study to determine if motor equivalence is a consistent underlying mechanism of expertise in striking sports.…”
Section: Discussionsupporting
confidence: 71%
“…For example, Pinder, Davids, and Renshaw (2012) studied the perceptual-motor coordination pattern of skilled cricket batsmen and found that when the length of delivery (ball landing position) was altered to require the batsmen to make a decision regarding the length of the ball they faced, various movement patterns were observed when the batsmen attempted to strike the ball. This observation of the flexibility and adaptability of visual perceptual-motor skill coordination is closely linked to the concept of motor equivalence, which refers to the equality of motor skill outcome or goal achievement from different movement patterns or muscle contractions (Mattos, Latash, Park, Kuhl, & Scholz, 2011;Mattos, Kuhl, Scholz, & Latash, 2013). Investigation of individual differences may explain whether different perceptualmotor coordination patterns can be used to achieve a similar goal of bat-ball interception in complex whole body striking skills.…”
mentioning
confidence: 99%
“…Several studies have shown that response to a perturbation happens to a large degree within the UCM, i.e., along directions with lower stability (Mattos et al 2011(Mattos et al , 2013Scholz et al 2000). So, a transient perturbation used in our study was expected to lead to deviations primarily along the UCM within the spaces of finger forces/modes.…”
Section: The Ucm Concept and Stability Of Actionmentioning
confidence: 95%
“…These differences can be probed using external changes in the force field Mattos et al 2011;Yang et al 2007) or using across-trials analysis of variance under the assumptions that natural variability results in varying initial conditions and changes in the timevarying state of the system (Scholz and Schöner 1999;Scholz et al 2000). The latter method has been primarily used to explore stability of redundant systems in support of the concept of the UCM (reviewed in Latash et al 2007).…”
Section: The Ucm Concept and Stability Of Actionmentioning
confidence: 99%
“…It is characterized as good because higher values of this index indicate more flexibility: the availability of varied movement patterns to accomplish the same task 4,21,22 . Such flexibility is very useful to deal with changing circumstances, such as unexpected perturbations 28 , fatigue of one of the elements 29 , and also secondary tasks 30 . Low V UCM is a sign of stereotypy 21 .…”
Section: Investigating Synergies With Ucm In Populations With Movemenmentioning
confidence: 99%